EMOTIONAL COMPETENCIES OF THE FORTHCOMING PHYSIOTHERAPISTS AND PHYSICAL EDUCATION TEACHERS - Anna Romanowska-Tolloczko (Physical Education of Students)
Purpose. Defining the level of emotional intelligence of students - prospective physiotherapists and physical education teachers. Material and method. The study was conducted amongst students of University School of Physical Education in Wrocław: There were 134 students from Physiotherapy Department and 254 students of Physical Education Department tested. In the research the tool to diagnose emotional intelligence was used: Emotional Intelligence Scale by Matczak et al. Results. In assessing the level of emotional intelligence the differences between students groups were pointed out due to their field of study and gender. Average emotional intelligence for all groups was at the moderate level although prospective teachers reached higher scores. Students of Physiotherapy and subjects constituting the control group showed lower level of studies parameter and the results were similar. Different levels of emotional intelligence are also visible in the results obtained by women and men. Women in each group receive higher scores than men. Conclusions. Emotional competencies of the subjects are at the moderate and low level, which is not a satisfactory result. Higher predispositions should be expected of people who choose teaching or physiotherapist professions, because it is required by specificity of the work they intend to carry on. Therefore, it seems necessary to pay special attention to the development of these competencies in the course of the study.